Status of the Waterbirds of Sunabeda Wildlife Sanctuary, Odisha, India - Lahkar, Dipankar; Sahu, H. K.; Ahman, S. R. (Indian Forester, 2013)
Population study of water birds was conducted in two wetlands 'Raital Bandh' and 'Jalkil Bandh' of the Sunabeda Wildlife Sanctuary, Odisha, India, in two successive years 2009 and 2010. 4,701 birds of 29 species belonging to 12 families were recorded during two years. Highest number of waterbirds were observed in Raital Bandh during both years. All total eight winter and twenty one resident species were identified during the study period. The family Anatidae (46.67% and 51.30%) in Raital Bandh and 60.79% and 58.14% respectively in Jalkil Bandh forms the main bulk of the waterbirds population. Species diversity was found highest in Raital Bandh in 2009 (1.398) and in 2010 Jalkil Bandh (1.342). The depth of the water and siltation was the major problem in winter of these two wetlands. Illegal activities like netting, killing of wild birds are continuously major threats for the conservation.